Mentalization Based Treatment (MBT): A Possible Theoretical Frame for Music Therapy Practice in Clinical Psychiatry - Hannibal, Niels; Schwantes, Melody (Voices: A World Forum for Music Therapy, 2017)
The mentalization based treatment (MBT) model may be a valuable theoretical perspective for music therapists to consider using with clients in need of mental health care, particularly those with borderline personality disorder. This article explores some of the basic principles of MBT and its application to music therapy. We have included a case study and reflections for further consideration. It is our hope that music therapists will begin to incorporate this model within their treatment and care of clients with psychiatric disorders.